Media Framing Analysis of President Prabowo Subianto’s Decision to Join the Board of Peace - Iriene Christina Estevien Tumiwa; Erik Akmal (CV. Publikasi Indonesia, 2026)
This study is motivated by differences in online media coverage regarding President Prabowo Subianto’s decision to join the Board of Peace, which has generated diverse interpretations in the public sphere. These differences indicate the existence of reality construction shaped by the media through the way information is presented. The purpose of this study is to analyze how online media frame the event and how meaning is constructed through news texts. This study employs the concept of media framing using the Zhongdang Pan and Gerald M. Kosicki model, which emphasizes the analysis of syntactic, script, thematic, and rhetorical structures in news texts. The method used is a qualitative approach with media text analysis techniques, where data were obtained through documentation of two news articles from Kompas.com and Tempo.co selected purposively based on relevance and differences in perspectives. The results show that Kompas.com frames the event with a moderate approach by emphasizing a balance between peace efforts and diplomatic risks, while Tempo.co highlights optimism toward peace efforts before presenting criticism at the end of the coverage. These differences are reflected in the structure of information presentation, narrative patterns, and language use that influence readers’ interpretations. This study concludes that the media play an active role in constructing reality, allowing a single event to be interpreted differently depending on the framing used in the news, and highlighting the importance of critical awareness in understanding media information.